In effossa terra - De Sanctis, Gianluca (Studi e materiali di storia delle religioni, 2014)
Death by burial, which counts several cases, not only within Roman culture, is not a random killing, and therefore has a specific cultural value. Burying a living person does not simply mean to kill him, death is a consequence, not the aim of live burial. While some cases can be classified as "foundation sacrifices" - the victim or a part of his body is interred in order to give stability and durability to the new construction - others have almost the flavor of an execution - think of the punishment that awaits the vestal incesta - others instead are configured as real acts of surrender to the powers of the underworld, achieved through the deposition of the offer made in specially dug holes in the ground (mundi). These kinds of practices, in addition to shedding light on some constitutive mechanisms of the language of sacrifice such as the ritual substitution, show how for the Romans the border that separated the world of the living from that of the dead was tenuous and permeable. (English)